Diabetes management during Ramadan amid Covid-19 pandemic - Tootee, Ali (Daru, 2020)
Management of fasting patients with diabetes during Ramadan has always posed a great challenge on clinicians. This year, Ramadan has coincided with the Covid-19 pandemic which per se can complicate diabetes care. Although patients with diabetes should be generally discouraged from fasting, those who insist to fact during the current Covid-19 pandemic should undergo strict risk assessment and receive thorough education. In patients with type 2 diabetes, administered antidiabetics and their dose should be modified to minimize the risk of hypoglycemia and dehydration. In type 1 diabetic patients, insulin dose and it timing should be precisely calculated based on regular and rigorous blood glucose monitoring. Nonetheless, it would be prudent to generally discourage patients with diabetes form fasting this Ramadan to avoid the risk of life-threatening complications such severe dehydration and ensuing kidney damage.